Transvestite M(other) in the Canadian North: Isobel Gunn by Audrey Thomas - Filipczak, Dorota (Text Matters: A Journal of Literature, Theory and Culture, 2018)
The article focuses on the eponymous protagonist of Isobel Gunn, a Canadian feminist historical novel by Audrey Thomas, published in 1999. Based on a real story, the novel fictionalizes the life of an Orcadian woman who made her transit from the Orkney Islands to the Canadian north in male disguise, and was only identified as a woman when she went into labour. The article juxtaposes the novel against its poetic antecedent The Ballad of Isabel Gunn, published by Stephen Scobie in 1983. In the article Gunn’s fate as a unique transvestite m(other) in the Canadian north is compared to the fate of famous transvestite saint Joan of Arc. Though removed from each another historically and geographically, both women are shown to have suffered similar consequences as a result of violating the biblical taboo on cross-dressing. Isobel’s sudden change of status from a young male colonizer to the defenseless colonized is seen in the context of managing the female resources by colonial authorities. At the same time, the fact that Isobel allows herself to be deprived of her son is analyzed in the light of insights on the maternal by Julia Kristeva and Luce Irigaray. The absence of the mother and the ensuing condition of her offspring’s orphanhood are shown as a consequence of reducing the position of the mother to that of an imperial servant, the fruit of whose body can be freely used and abused by the male imperial authority.